Bifunctional, Copper-Doped, Mesoporous Silica Nanosphere-Modified, Bioceramic Scaffolds for Bone Tumor Therapy - Ma, Hongshi; Ma, Zhenjiang; Chen, Qufei; Li, Wentao; Liu, Xiangfei; Ma, Xiaojun; Mao, Yuanqing; Yang, Han; Ma, Hui; Wang, Jinwu (Frontiers in Chemistry, 2020)
In the traditional surgical intervention procedure, residual tumor cells may potentially cause tumor recurrence. In addition, large bone defects caused by surgery are difficult to self-repair. Thus, it is necessary to design a bioactive scaffold that can not only kill residual tumor cells but also promote bone defect regeneration simultaneously. Here, we successfully developed Cu-containing mesoporous silica nanosphere-modified β-tricalcium phosphate (Cu-MSN-TCP) scaffolds, with uniform and dense nanolayers with spherical morphology via 3D printing and spin coating. The scaffolds exhibited coating time- and laser power density-dependent photothermal performance, which favored the effective killing of tumor cells under near infrared laser irradiation. Furthermore, the prepared scaffolds favored the proliferation and attachment of rabbit bone marrow‐derived mesenchymal stem cells and stimulated the gene expression of osteogenic markers. Overall, Cu-MSN-TCP scaffolds can be considered for complete eradication of residual bone tumor cells and simultaneous healing of large bone defects, which may provide a novel and effective strategy for bone tumor therapy. In the future, such Cu-MSN-TCP scaffolds may function as carriers of anti-cancer drugs or immune checkpoint inhibitors in chemo-/photothermal or immune-/photothermal therapy of bone tumors, favoring for effective treatment.